Development and application of processing techniques for signal enhancement using multisystem resistivity measurements - Kamkar-Rouhani, Abolghasem (Curtin University, 1998)
DC electrical surveying involves the injection of current into the earth, and the measurement of the electrical potential differences this produces. A number of electrode configurations such as the Schlumberger and Wenner arrays, dipole-dipole and pole-pole geometries are in common use for electrical surveying. New acquisition systems enable the convenient collection of data with a number of common configurations at the same time. It is found however that while the recovery of layered structure from electrical surveys can be effective, the sensitivity and resolving power of such systems in detecting the presence of anomalous three-dimensional (3-D) bodies is poor. This is mainly due to the dominance of conduction pathways through the layered earth compared to the influence of small 3-D conductivity anomalies.Theoretical relationships between the responses of various survey geometries to the layered earth may be established as is shown in this thesis, but their response to 3-D targets differs strongly. This thesis introduces a new procedure for anomalous target detection by the computation of an apparent resistivity residual using multi-electrode configuration survey data. This procedure, applicable to a variety of electrode geometries, reduces the dominance of the layered earth response and enhances the signal from 3-D structures.In the development and testing of this new apparent resistivity residual, numerically modelled data were used. In order to obtain suitable test data of high accuracy it was necessary to make improvements to modelling software. For this purpose, recently developed techniques in numerical modelling such as the biconjugate gradient method, new digital linear filters for computation of Hankel transforms, and spectral formalism were employed in an integral equation approach for the software developed in this thesis.The computed apparent resistivity residual was found to depend on the array type and dimensions, the nature of the anomalous zone, geological layer geometries, and resistivity contrasts of the layers involved. While the apparent resistivity residual signature requires some measure of interpretation, it is shown to enhance the resolution and detectability of 3-D targets in a layered environment.The presence of random noise produces some degradation in the performance of the residual technique, but a normalisation procedure has been developed to alleviate the problem. A preliminary field trial showed that survey profiles of apparent resistivity residual were able to locate a subsurface conductive anomaly in an area in Western Australia.A transitional zone is defined as a layer in the earth where resistivity varies as a continuous function of depth. A theoretical formulation for the electrical response of an earth structure composed of anomalous 3-D bodies in the presence of transitional layers is introduced. Tests on synthetic survey data showed that the apparent resistivity residual is an effective anomaly detector in transitional layer environments.A multi-system method of computing an apparent resistivity residual has been developed theoretically and tested on both synthetic and field data. This new approach when applied to resistivity profiling is more sensitive to, and gives greater resolution of, localised anomalies than is possible using conventional profiling procedures.